Analysis of the stresses in the interface between dry-set mortar and ceramic tiles under thermic efforts - Saraiva, Ana Gabriela (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
Building façades may be affected by different kinds of pathologies. Coating displacement usually happens either between interface ceramic tiles and dry-set mortar or between this mortar and the rendering. This work presents the results of a study based on the Finite Element Method, in which, starting from the numerical model defined for analysis, the stresses in the interface between dry-set mortar and ceramic tiles under thermic efforts were examined. These efforts were analysed with dry-set mortar in three different situations: by changing the thickness of the rendering, the thermal absorption coefficient of tiles and the ceramic tile grout used in the façade model studied. It is possible to observe that when the thickness of the rendering increases, there is a slight reduction of normal stresses throughout the Y axis. Moreover, stresses increase approximately 60% when ceramic tiles with higher absorption coefficient are used. The use of ceramic tile grout with lower elasticity modulus produces higher normal stresses throughout Y axis in joint areas and lower stresses in the centre of the ceramic tiles, which are submitted to a flexural effort. This result reinforces the importance of the test for determining the flexural resistance modulus, as described by Brazilian standards.